Integrasi Pendidikan Bahasa Arab Tradisional dan Metode Modern dalam Kurikulum Bahasa Arab Murni - Ismail Akzam; Najmi Hayati (CV Najmi Edu Creative, 2026)
The transformation of education and the demands of 21st-century competencies demand linguistically strong Arabic language learning, as well as being communicative and adaptive to technology. Traditional education in Islamic boarding schools and kuttabs has advantages in mastering turats, thoroughness of nahwu–sharaf, memorization, talaqqi, and sanad. In contrast, modern methods, such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and blended learning, are effective in enhancing communicative competence and promoting independent learning. This article aims to identify the characteristics of traditional Arabic education, assess the relevance of modern methods, and formulate an integrative curriculum model for pure Arabic language instruction. The research employs a qualitative-descriptive design, utilizing an integrative literature review that is thematically analyzed in light of sociocultural theory, constructivism, educational linguistics, and Fogarty's curriculum integration model. The results showed that traditional approaches excelled in language deepening and adab formation, but were weak in communication and ICT utilization; In contrast, modern approaches enhance practical skills but can reduce the deepening of turats if they are not balanced. The synthesis of the two resulted in an integrative curriculum model that combines talaqqi, memorization, and book study with communicative tasks, collaborative projects, and the use of digital platforms. This model offers a practical framework for institutions to maintain the purity of the Arabic language while meeting the demands of contemporary learning.